STRUKTUR KOMUNITAS GASTROPODA DI KAWASAN KONSERVASI MANGROVE DAN BEKANTAN (KKMB) KOTA TARAKAN - Septiani, Fanny; Wiharyanto, Dhimas (Jurnal Harpodon Borneo, 2015)
Gastropods are mollusk  animals, generally live on the surface of the substrate of mud and there is attached to the leaves and roots of mangrove which are also in the Mangrove Conservation Area and Bekantan (KKMB) Kota Tarakan. These organisms contribute greatly to the organic detritus that is very important as a food source for organisms that live in the surrounding waters. The purpose of this study to determine the structure of gastropods community include diversity index, dominance index, and the index of uniformity in the Mangrove Conservation Area and Bekantan (KKMB).The method used in this research is the method dekskriptif with survey techniques to determine the research station on the terms of the condition of mangrove.From theresearch, was found 25 species of gastropods associated mangrove forest KKMB Tarakan City. At the first station, the species gastrophod withthe highest abundanceis Neritina violaceaand the lowestisNeritalineta. At station 2, the type gastrophoda with the highest abundance is Shaerassiminea miniata and the lowest is Nerita lineta.The index valueof diversity at each station ranged between 2.72 and 2.92. With this value range indicates that the abundance gastrophoda in KKMB is medium category. Uniformity index value at each station of 0.91 and 0.92, which means the number of individuals spread evenly or no dominatingre inforced with dominance index value at each station 0.07 and 0.08 (close to zero).Key Words : Mangrove, Gastropod dan Community Structure.